2010
DOI: 10.1038/ng.732
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies susceptibility loci for polycystic ovary syndrome on chromosome 2p16.3, 2p21 and 9q33.3

Abstract: Polycystic ovary syndrome (PCOS) is a common metabolic disorder in women. To identify causative genes, we conducted a genome-wide association study (GWAS) of PCOS in Han Chinese. The discovery set included 744 PCOS cases and 895 controls; subsequent replications involved two independent cohorts (2,840 PCOS cases and 5,012 controls from northern Han Chinese; 498 cases and 780 controls from southern and central Han Chinese). We identified strong evidence of associations between PCOS and three loci: 2p16.3 (rs134… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
456
6
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 641 publications
(503 citation statements)
references
References 32 publications
24
456
6
17
Order By: Relevance
“…The fact that most differentially expressed lncRNAs (n=74) were transcribed from chromosome 2 is remarkable. Notably, a recent genome-wide association study (GWAS) identified three of 11 susceptibility loci for PCOS on chromosome 2, including the 2p16.3 (rs13405728), 2p21 (rs13429458), and FSHR genes [1,43]. Our data and previously published studies suggest that the genes located on chromosome 2 play important roles in the development and progression of PCOS.…”
Section: Discussionsupporting
confidence: 66%
“…The fact that most differentially expressed lncRNAs (n=74) were transcribed from chromosome 2 is remarkable. Notably, a recent genome-wide association study (GWAS) identified three of 11 susceptibility loci for PCOS on chromosome 2, including the 2p16.3 (rs13405728), 2p21 (rs13429458), and FSHR genes [1,43]. Our data and previously published studies suggest that the genes located on chromosome 2 play important roles in the development and progression of PCOS.…”
Section: Discussionsupporting
confidence: 66%
“…Despite the semblance to an autosomal dominant inheritance, an oligogenic/polygenic model most likely contributes to the underlying pathophysiology (23,24). Incomplete penetrance, epigenetic modification, and environmental contributions have hindered attempts to clarify the underlying model of inheritance.…”
mentioning
confidence: 99%
“…The first genome-wide association studies (GWAS) and subsequent follow up performed on Han Chinese populations identified the following PCOS candidate loci: DENND1A, insulin receptor (INSR), YAP1, C9orf3, RAB5B, HMGA2, TOX3, SUMO1P1/ZNF217, THADA, follicle stimulating hormone receptor (FSHR), luteinizing hormone/choriogonadotropin receptor (LHCGR) (23,24). The identification of the DENND1A locus at 9q22.32 has been replicated in both Asian and European populations (26)(27)(28)(29), hence DENND1A has gained recognition as a strong PCOS susceptibility gene (30).…”
mentioning
confidence: 99%
“…40 A recent GWAS and replication study identified three new susceptibility loci on chromosome 2p16.3, 2p21 and 9q33.3 and a novel YAP1 gene for PCOS in Han Chinese. 10,41 We also evaluated the significance in the previously reported 7 genome-wide significant loci for PCOS (rs13405728 at 2p16.3; rs12468394, rs13429458 and rs12478601 at 2p21; rs10818854, rs2479106 and rs10986105 at 9q33.3). Except for rs2479106 in DENND1A, the six of seven SNPs had a significant P-value between 2 Â 10 À2 and 8 Â 10 À4 .…”
Section: Resultsmentioning
confidence: 99%
“…5,6 However, because of differential diagnostic criteria and unclear etiology of PCOS, it can be difficult to find reproducible associations from diverse racial and ethnic background. [7][8][9] Although a recent genome-wide association study (GWAS) has contributed to susceptibility genes or loci discovery for PCOS, 10 identifying a major determinants underlying variation in primary metabolism would be more valuable. [11][12][13] PCOS and T2D are obesity-related conditions that share epidemiological and pathophysiological factors.…”
Section: Introductionmentioning
confidence: 99%